Anaerobic accumulation of short-chain fatty acids from algae enhanced by damaging cell structure and promoting hydrolase activity. (February 2018) - Feng, Leiyu; Chen, Yunzhi; Chen, Xutao; Duan, Xu; Xie, Jing; Chen, Yinguang
Graphical abstract: Highlights: Short-chain fatty acids were produced efficiently during algae anaerobic fermentation at pH 10.0. Acetic and iso -valeric acids were the dominant products from algae. Cell structure of algae was destroyed and activities of hydrolases were improved at alkaline pHs. Microcystins from algae were removed effectively during anaerobic fermentation at pH 10.0. Abstract: Short-chain fatty acid (SCFAs) produced from harvested algae by anaerobic fermentation with uncontrolled pH was limited due to the solid cell structure of algae. This study, therefore, was undertaken to enhance the generation of SCFAs from algae by controlling the fermentation pH. pH influenced not only the total SCFAs production, but the percentage of individual SCFA. The maximal yield of SCFAs occurred at pH 10.0 and fermentation time of 6 d (3161 mg COD/L), which mainly contained acetic and iso -valeric acids and was nearly eight times that at uncontrolled pH (392 mg COD/L). Mechanism exploration revealed at alkaline pH, especially at pH 10.0, not only the cell structure of algae was damaged effectively, but also activities and relative quantification of hydrolases as well as the abundance of microorganisms responsible for organics hydrolysis and SCFAs production were improved. Also, the released microcystins from algae were removed efficiently during alkaline anaerobic fermentation.